2016
DOI: 10.4269/ajtmh.15-0864
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Botswana Children Under 2 Years Old With and Without Active Tuberculosis

Abstract: Abstract. Additional strategies are needed to prevent and treat tuberculosis (TB). Although vitamin D may have antimycobacterial effects, it is unknown whether low vitamin D status confers a risk for active TB in African children. This case-control study assessed serum 25-hydroxyvitamin D (25(OH)D) concentration in children with and without active TB in Gaborone, Botswana. A total of 80 children under 2 years old with and without active TB, seen at hospitals and clinics in the greater Gaborone area between Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Four studies [2023] described the difference in 25(OH)D levels in children with TB and controls; two [21,23] of these studies calculated 25(OH)D levels in nmol/L, and two [20,22] calculated 25(OH)D levels in ng/mL. Four studies [2427] evaluated the association between the presence of any TB and VDD. One study [25] showed a significant association between the presence of any TB and VDD, while 2 studies [24,25] showed a significant association between the presence of active TB and VDD; however, 3 studies [24,26,27] showed a nonsignificant association between the presence of any TB and VDD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies [2023] described the difference in 25(OH)D levels in children with TB and controls; two [21,23] of these studies calculated 25(OH)D levels in nmol/L, and two [20,22] calculated 25(OH)D levels in ng/mL. Four studies [2427] evaluated the association between the presence of any TB and VDD. One study [25] showed a significant association between the presence of any TB and VDD, while 2 studies [24,25] showed a significant association between the presence of active TB and VDD; however, 3 studies [24,26,27] showed a nonsignificant association between the presence of any TB and VDD.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [2427] evaluated the association between the presence of any TB and VDD. One study [25] showed a significant association between the presence of any TB and VDD, while 2 studies [24,25] showed a significant association between the presence of active TB and VDD; however, 3 studies [24,26,27] showed a nonsignificant association between the presence of any TB and VDD. Four studies [22,23,28,29] showed that VDD contributes to TB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No infants were deficient, regardless of whether infants were breastfed or not, and although mothers with HIV-infants had significantly higher 25(OH)D concentrations, there were no significant differences in 25(OH)D concentrations between HIV+ and HIV-infants. This was an unexpected finding given the group of mothers with insufficient vitamin D concentrations and breastfed infants, which supplies minimal vitamin D. Another study in Botswana reported 19% of infants and children under 2 years (n = 80) with and without tuberculosis were vitamin D insufficient [27] and a study in otherwise healthy Tanzanian infants reported 76% had insufficient vitamin D [28]. HIV + infants in the present study had significantly greater 1,25(OH)D compared to HIV-, however, 1,25(OH)D is not considered a good surrogate for vitamin D status [29] and so the implications of this difference are unclear.…”
Section: Plos Onementioning
confidence: 95%
“…On the other hand, two studies found no correlation between TB cases and vitamin D [41,42]. The first evaluated serum 25(OH)D concentrations in infants and toddlers aged < 5 years with and without active TB in Pune India and found that both groups were equally vitamin D deficient at a high percentage.…”
Section: Vitamin D and Tuberculosismentioning
confidence: 99%